Comparative study of CA19-9 levels as tumor marker in sera and tissues of patients with stomach, colon and rectum cancers - Al-dujaili, Amar H.; Al-Taei, Wafaa F.; Turky, Kisma M; Al-Ubaidi, Gheid H. (Journal of the Faculty of Medicine Baghdad, 2009)
Background: CA19-9 is among a group of mucin glycoprotein sialosyl lewis antigen (SLA) having come to be recognized as a circulating cancer associated antigen for gastrointestinal cancer. Basic research into cancer causation will be a powerful determinant of intervention in the transformation process reinforcing the need for developing effective molecular tumor biomarkers for early detection of malignant evolution in tissues of organs i.e. stomach, colon and rectum. In this study, we make a comparsion between the levels of CA19-9 in sera and tissues of patients with these diseases to see if their levels are proportional and if it is a tumor marker that affect with malignant cells in tissues of these organs.Patients and methods: Carbohydrate antigen 19-9 (CA19-9) levels were measured in sera and tissues’ of 8 patients with stomach cancer (G1), 8 patients with colon cancer(G2), 8 patients with rectum cancer (G3) and 30 healthy subjects (G4), by the enzyme-linked immunosorbent assay (ELISA) technique.Results: The results of CA19-9 levels in sera were (42.625±33.088; 47.013±0.318 and 10.938±0.979)U/ml for G1, G2 and G3 respectively compared with serum CA19-9 level of G4, whichwas 7.74±4.92 U/ml. The results were found to be significantly higher than control group (p